Modules for Practices with Microcontrollers: PIC16F88 and ATMega328 on Arduino - Sanchez, Luis Gil; Civera, Javier Ibanez; Pinatti, Cristian Olguin; Bellver, Maria Auxilio Recasens (Technologies Applied to Electronics Teaching (Online), 2024)
In this communication, several modules are presented to carry out practices with a microcontroller, initially with the PIC16F88, which was later conditioned to be used by the ATMeg328 on the Arduino UNO platform. Finally, a new module is presented with the ATMega328, but on the Arduino NANO platform. The practice modules consist of a printed circuit board where the necessary components are incorporated to carry out the practices planned with this device in the Digital Electronics subject. In this way, time is saved in assembly and security is gained in operation, so that the student can focus on the programming and operation of the device. These boards have been used for several years with numerous students and have worked perfectly.